International Monetary Fund Annual Report 1947. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1947)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended June 1947. The report highlights that in the two years since the end of the Second World War, considerable progress has been made toward rebuilding the economies of the devastated and disrupted countries, although the work is far from complete. A number of countries in Europe have succeeded in approaching or even exceeding the pre-war levels of industrial production, but in others, output still lags far behind.